La azarosa integración europea en la última década y el significado del Tratado de Lisboa - Pereira Menaut, Antonio Carlos (Revista de Derecho, 2019)
It is possible that the Lisbon Treaty is a typical product from the European legislative factory. Whether it is true that it contains novelties, it is not probable that it will break with the traditional Continental European constitutionalism. From the point of view of the types of integration the matter remains open; the Lisbon Treaty has not closed it since there are diverse ways of integration to form a greater union, and that is a topic of higher importance to the future of Europe.
Keywords: Constitucionalism; integration; Lisbon Treaty; European Union; Community Law